Effects of L-thyroxine and zinc therapy on wound healing in hypothyroid rats - Erdogan, M; Ilhan, YS; Akkus, MA; Caboglu, SA; Özercan, I; Ilhan, N; Yaman, M (Assoc Soc Scientifique Med Belges, 1999)
Unfavourable effects of hypothyroidism and zinc deficiency on wound healing are well known. This experimental study was conducted on rats to evaluate the effects of hormone replacement and zinc supplement on wound healing. A total of 50 rats were divided into 5 groups of 10 rats as follows: Control group (A), a hypothyroidism group (B), a L-thyroxine receiving hypothyroidism group (C), a zinc receiving hypothyroidism group (D), and a L-thyroxine plus zinc receiving hypothyroidism group (E). In order to develop hypothyroidism, 5-propyl 2-thiouracil had been given intraperitoneally for a period of 21 days to all groups except the control group. A laparotomy with a 4 cm median incision was performed in all rats. The first half of the rats was sacrificed on the 7(th) day and the remaining on the 14(th) day. Breaking strength, hydroxyproline concentrations in the healing scar tissue and blood serum zinc levels were measured. Although both values - breaking strength and hydroxyproline levels -, compared to all others, were found to be higher in the L-thyroxine plus zinc receiving group (group E) on the 7(th) day, differences among the groups were not statistically significant. However, on the 14(th) day, these differences were found to be significant. We conclude that the hormone replacement therapy in hypothyroidism cases was beneficial with regard to wound healing and the results were more satisfactory if zinc was added to the therapy.
Keywords: hypothyroidism; wound healing; L-thyroxine; zinc deficiency; breaking strength; hydroxyproline